Análise de necessidades e gêneros de texto para o planejamento de material didático de espanhol para fins específicos: o curso técnico em transações imobiliárias - Labella-Sánchez, Natalia (Universidade do Vale do Rio dos Sinos, 2016)
This qualitative research focuses on the design and conceptualization of learning materials aimed at the teaching of Spanish for specific purposes based on genres for the subsequent modality course of a Federal Institute in the southern of Brazil: the course of Technician in Real Estate. Because vocational education courses aim to train and professionally qualify students, they provide the right context for the teaching of languages for specific purposes (LSP). For courses of LSP, it is essential to carry out a needs analysis that supports the design and conceptualization of learning materials aimed to meet the specific professional and academic needs of students (HUTCHINSON; WATERS, 1996). Thus, with the intent to conceptualize a didactic proposal for the teaching of Spanish based on genres for vocational education courses, the concept of genres have been considered since the needs analysis stage in the research. The theoretical foundations used to support such an analysis come from the Rhetorical Genre Studies, specially, the theoretical and methodological proposal of the study of activity systems (BAZERMAN, 2005) to identify and comprehend the genres that circulate in a specific socio-communicative context. For the stage of analysis and didactization of the characteristics of the identified genres, the theoretical and methodological framework of the Sociodiscursive Interactionism (SDI) has been used, more specifically the proposal of didactization of language capacities needed for the production and/or consumption of genres, based on the production of didactic sequences (SCHNEUWLY, 1998; 2004; DOLZ; SCHNEUWLY, 1998; SCHNEUWLY; DOLZ, 2004a, DOLZ; NOVERRAZ; SCHNEUWLY, 2004). The corpus was generated through surveys and semi-structured interviews, field notes and the gathering of exemplars of genres. Among the methodological procedures adopted to analyse the activity systems of the real estate agents, Bazerman’s methodological proposal (2005) and the techniques and procedures of grounded theory to code, categorize and relate pieces of information were used (STRAUSS; CORBIN, 2008; CHARMAZ, 2009). In relation to the analysis of the didactic characteristics of the genres identified, the methodological suggestions of the SDI framework were used (DOLZ; SCHNEUWLY, 1998; CRISTOVÃO et al., 2010; CRISTOVÃO; STUTZ, 2011). The findings indicate that the analysis of the activity systems of real estate agents of Porto Alegre and the identification of the genres in Spanish that can be used by such professionals, to engage with Hispanic-speaker clients, generated relevant informative subsidy to: (a) know the language capacities, especially those of the pre-textual level of analysis, that constitute the genres in Spanish; (b) guide the design of Spanish teaching material for real estate agents based on didactic sequences; (c) produce instructions and activities that explore the language capacities characteristic of genres based on the socio-communicative situations needed for their production and/or consumption. The study allowed the conclusion that the relation of intersection and complementarity between the study of activity systems (BAZERMAN, 2005) and the proposal of didactization of SDI have potential to subsidize the design of learning materials for the teaching of languages for specific purposes.
Keywords: Ensino de espanhol para fins específicos; Análise de necessidades; Gêneros de texto; Planejamento de material didático; Sequências didáticas; Spanish teaching for specific purposes; Needs analysis; Genres; Design of learning materials; Didactic sequences; ACCNPQ::Lingüística, Letras e Artes::Lingüística